Influência de parâmetros físicos e do processamento digital utilizado nos sinais oriundos do ensaio charpy instrumentado - Manoel, Paulo Afonso Franzon [UNESP] (2012)
In this work, was the influence of physical parameters evaluated (stiffness of the striker, length of the specimen, the geometry of the striker) on the magnitude of the interference present in the curves load vs. time and load vs. displacement, the effect of various filters on the signal obtained was also studied. In this study, instrumented strikers (like load cells) of different stiffness and were used a striker which has a different geometry than the others was also tested. Furthermore, the tests were conducted with specimens with length equal to 55 mm (according with ASTM E-23), 70 mm and 85 mm. The data were processed by these digital filters: low pass, high pass, band pass and moving average. The spectrums of the filtered signals were compared with the original ones. The results showed that the stiffness of the striker has an inverse relation with the magnitude of the interference. On the other hand, the length of the specimen has a direct relation with the increased level of interference, the striker with different geometry also exerted influence on the load vs displacement curve. The moving average filter has been a good way out in the treatment of data, but is necessary to use a limited number of points in order not to eliminate essential components of the signal which contains information about the deformation and fracture process. For the materials used in this work, the signal spectrum is between 100 Hz and 50 kHz, but the range between 10 kHz and 50 kHz is predominantly responsible for the interference components.